Clinical Characteristics, Renal Involvement, and Therapeutic Options of Pediatric Patients With Fabry Disease - Muntean, Carmen; Starcea, Iuliana Magdalena; Stoica, Cristina; Banescu, Claudia (Frontiers in Pediatrics, 2022)
Inherited renal diseases represent 20% of the causes of end-stage renal diseases. Fabry disease, an X-linked lysosomal storage disorder, results from α-galactosidase A deficient or absent activity followed by globotriaosylceramide (Gb3) accumulation and multiorgan involvement. In Fabry disease, kidney involvement starts early, during intrauterine life by the Gb3 deposition. Even if chronic kidney disease (CKD) is discovered later in adult life in Fabry disease patients, a decline in glomerular filtration rate (GFR) can occur during adolescence. The first clinical sign of kidney involvement is represented by albuminuria. So, early and close monitoring of kidneys function is required: albuminuria and proteinuria, urinary albumin-to-creatinine ratio, serum creatinine, or cystatin C to estimate GFR, while urinary sediment with phase-contrast microscopy under polarized light may be useful in those cases where leucocyte α-Gal A activity and GLA genotyping are not available. Children with Fabry disease and kidney involvement should receive enzyme replacement therapy and nephroprotective drugs (angiotensin-converting enzyme inhibitors or angiotensin receptor blockers) to prevent or slow the progressive loss of kidney functions. Early diagnosis of Fabry disease is important as enzyme replacement therapy reduces symptoms, improves clinical features and biochemical markers, and the quality of life. More importantly, early treatment could slow or stop progressive organ damage in later life.